Investigating Socio-Economic and Academic Consequences of Insecurity and Kidnapping in Senior Secondary Schools in Anambra State - Rose Nwakaego Umezinwa (Journal of Education and Teacher Training Innovation, 2024)
The study investigates the socio-economic and academic consequences of kidnapping in senior secondary schools in Anambra State.  Two research questions and two research hypotheses were formulated for the study. The scope was restricted to the extent to which kidnapping influence academic performance and socio-economic development of students. Relevant literatures were reviewed on conceptual framework, theoretical framework, empirical studies and summary of reviewed literature. The design of the study was a descriptive survey design. The study was carried out in Anambra State. The study population was public SS 2 students in Anambra State. The sample of the study consisted of 400 SS2 students. The instrument for the study was a questionnaire consisting of 10 items. The instrument was validated by 3 experts – two experts in measurement and evaluation and one expert in administration. The reliability of the instrument was done using Pearson Product Moment Correlation (r) yielding a value of 0.86. Data analysis was conducted using mean and standard deviation for research question and t-test statistic was used to test the research hypotheses. The results of the study were as follows: there is a significant difference between the mean ratings to which kidnapping influence academic performance of SS2 students in senior secondary schools and there is a significant difference between the mean ratings to which kidnapping influence socio-economic development of SS2 students in senior secondary schools. The study recommended among others that government and traditional rulers should encourage dialogue and conflict resolution mechanisms at the community level to address underlying grievances and prevent conflicts from escalating into violence.